Online search interest in major depressive disorder: Infodemiology study using the most visited search engine in Japan - Rikako Shimizu; Kosuke Ishizuka; Kagami Kobayakawa; Taiju Miyagami; Mizue Saita; Hirotake Uchikado; Tomoki Yamada; Tomoya Sakama; Akihiko Kusakabe; Mitsuyasu Ohta; Toshio Naito (PLoS ONE, 2026)
Individuals with major depressive disorder (MDD) have an increased risk of suicide and work impairment; therefore, providing appropriate treatment as soon after the onset as possible is critically important. Previous studies on public interest in MDD based on online search trends have addressed temporal changes and regional differences, whereas analyses focusing on the content of search queries remain limited. This study aimed to describe online search trends on MDD in Japan and investigate the relationship between societal perceptions of depression and the symptoms constructs in clinical diagnosis. We conducted a descriptive observational study using the search volume of queries containing “Utsu-byou” (Depression; Major Depressive Disorder in Japanese) from January 2022 to December 2024 using data obtained from Yahoo! JAPAN. We compared the search volume for the top 500 queries on depression each year, and the search volume of queries of symptoms co-searched with depression. These symptoms were classified according to “Component 1—Symptoms and complaints” of the International Classification of Primary Care, 2nd edition (ICPC-2). Furthermore, symptoms classified based on the ICPC-2 were categorized according to whether they corresponded to the diagnostic criteria for MDD in the Diagnostic and Statistical Manual of Mental Disorders, Fifth Edition (DSM-5-TR). The search volume for “Depression symptoms” was higher than that for “Depression” alone. Many of the symptoms co-searched with depression corresponded to the diagnostic criteria for MDD in the DSM-5-TR. Specifically, sleep disturbance, which is also frequently observed in clinical practice, was the most frequently co-searched symptom. Public perceptions online of depressive symptoms may demonstrate a certain degree of consistency with clinical diagnostic concepts. Online search data may help clinicians understand how patients recognize and frame depressive symptoms in primary care settings.